Geochemistry of fluorine in halo waters of ore fields of the southeastern part of the Dnipro-Donetsk avlakogen - Suyarko, Vasyl; Sasmaz, Ahmet; Bartaschuk, Oleksii; Ukova, Olga Serd.; Manyuk, Volodymyr (V N Karazin Kharkiv Natl Univ, 2022)
The geochemical features of fluorine and its possible sources in the waters of the hydrothermal ore fields of the Dnipro-Donetsk avlakogen (DDA) are considered. It was established that the formation of anomalies occurs due to the interaction of infiltration waters of the zone of free water exchange and waters of deep formation, which are unloaded along the zones of deep faults. It is substantiated that the water migration of fluorine is determined by the geochemical type of groundwater, the degree of its mineralization, acid-base (pH) and oxidation-reduction (Eh) potentials, the presence of complex-forming elements with which fluorine forms mobile complex compounds, etc. Formulation of the problem. Fluorine is a typomorphic chemical element that is widely present in groundwater. It forms large-scale, contrasting hydrogeochemical anomalies in various types of hydrothermal ore fields, which are controlled by zones of deep faults - fluorite, mercury, polymetallic, and others. Presenting main material. Anomalies of the element are also formed in those fault zones, where the processes of modern heat and mass transfer are observed, manifested in the upward discharge of endogenous fluids against the background of increased intensity of the geothermal field. This indicates the probable arrival of fluorine in endogenous fluid flows, which are mixed with formation waters during their upward migration. The most contrasting aureoles of fluorine scattering are established in the zone of hypergenic weathering of fluorite of the Pokrovo-Kyreevsky deposit and in the aureole waters of the Mykytiv mercury ore field, in the rocks of which fluorite mineralization is absent. In them, fluorine, together with other trace elements, forms multicomponent anomalies and is part of the hydrogeochemical association of elements-indicators of hidden mercury mineralization - Hg, As, B, F, (Sb). Conclusions. 1. Geochemical features of fluorine in the processes of hydrothermal mineralization are caused by both hypogenic and hypergenic factors of its migration and concentration in the hydrolithosphere of the Dnipro-Donetsk avlakogen. 2. The high migration activity of fluorine in fluid systems and, in particular, in groundwater, is determined by numerous mobile forms of the element that exist under different geochemical conditions - in the form of gas, simple anions, complex compounds with metals, silicon, manganese, boron and other chemical elements Fluorine migrates best in alkaline sodium bicarbonate and sodium chloride waters, in which.l-, Na+ and..- ions not only act as a complexing agent, but also provide high ionic strength of aqueous solutions. 3. The high content of fluorine in the waters of the Pokrovo-Kyreivsky fluorite deposit is provided by two different geochemical processes: a) hypergenic physicochemical destruction of CaF2 by gravitational infiltration waters of the zone of free water exchange; b) the influx of fluorine into deep formation waters together with endogenous fluids that are discharged along fault structures at the post-hydrothermal stage of their tectonic activation. 4. Abnormally high concentrations of fluorine in the hydrothermal mercury ore fields of the Mykytivskyi and Druzhkivsko-Kostiantynivskyi deposits, in the rocks of which there is practically no fluorite mineralization, are due to the influx of the element into the mineralization zones from deep fluid flows and underground waters of deep horizons. 5. The main natural sources of fluorine in the waters of hydrothermal deposits of the region are: a) products of hypergenic weathering of hydrothermal mineralization of fluorite; b) flows of endogenous postheterothermal fluids; c) pore solutions of sedimentary rocks of marine origin.
Keywords: fluorine; halo waters; fault zones; hydrothermal ore fields; hydrogeochemical anomalies; fluid flows; heat and mass transfer; water migration